2012
DOI: 10.1113/expphysiol.2012.067256
|View full text |Cite
|
Sign up to set email alerts
|

Melanocortin 3/4 receptors in paraventricular nucleus modulate sympathetic outflow and blood pressure

Abstract: New findings r What is the central question of this study?The paraventricular nucleus (PVN) is important in regulating sympathetic activity and blood pressure. This study addresses whether activation of melanocortin 3/4 receptors in the PVN modulates sympathetic activity and blood pressure, and whether intracellular signalling involves the cAMP-protein kinase A pathway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
48
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(50 citation statements)
references
References 47 publications
2
48
0
Order By: Relevance
“…We observed that mDMHGsKO mice had reduced heart rate, but normal blood pressure. In contrast, mice with whole-brain and PVN-specific Gnas knockout have both decreased heart rate and blood pressure (9), consistent with G s α pathways in the PVN being the primary mediator of MC4R effects on blood pressure (27,39). The present results suggest that G s α signaling in different hypothalamic nuclei plays different roles in regulating cardiovascular function.…”
Section: Discussionmentioning
confidence: 37%
“…We observed that mDMHGsKO mice had reduced heart rate, but normal blood pressure. In contrast, mice with whole-brain and PVN-specific Gnas knockout have both decreased heart rate and blood pressure (9), consistent with G s α pathways in the PVN being the primary mediator of MC4R effects on blood pressure (27,39). The present results suggest that G s α signaling in different hypothalamic nuclei plays different roles in regulating cardiovascular function.…”
Section: Discussionmentioning
confidence: 37%
“…In the mouse DMH, we observed a significant number of RVLM-projecting neurons; however, the number was far smaller than when the CtB injections encompassed the raphe pallidus significant decreases in SNA, MAP, and HR, because NPY inhibits a G protein-activated inwardly rectifying K (GIRK) current (39-41), which can hyperpolarize to a greater extent than GABA A receptors, which open Cl channels. While the limited inhibition by GABA was expected, the effect of PVN AgRP on SNA in rats is controversial (8,42). Here, we show that doses of PVN AgRP that exceed those required to elicit food intake and sufficient to decrease body temperature failed to decrease SSNA, AP, or HR.…”
Section: Discussionmentioning
confidence: 76%
“…This AAR has been extended recently to other WAT pads, but with renal sympathetic nerve activity increases (adipose afferent renal reflex, AARR) with related changes in blood pressure and other cardiovascular responses (19,22,35,42,55,66,67).…”
Section: R896mentioning
confidence: 99%